NEW FORMATION TYPE OF CARBONATITES IN THE SEVAN OPHIOLITE ZONE (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
In the article genetical problems of carbonatites of the Sevan ophiolite zone are discussed. According to the authors, carbonatites are genetically related to hyperbasites and are a new formation type of mantle rocks, which absolutely differ from classic carbonatites of alkaline ultrabasite complexes. The issue of impossibility of the occurrence of alkali-ultramafites and alkali-carbonatites from depleted of alkali elements magma of the upper mantle has been discussed.
Keywords: carbonatite; ophiolite; ultrabasite; alkaline-carbonatite complexes; magmatic origin